2016
DOI: 10.1142/s0219498816500845
|View full text |Cite
|
Sign up to set email alerts
|

Leavitt path algebras satisfying a polynomial identity

Abstract: Abstract. Leavitt path algebras L of an arbitrary graph E over a field K satisfying a polynomial identity are completely characterized both in graphtheoretic and algebraic terms. When E is a finite graph, L satisfying a polynomial identity is shown to be equivalent to the Gelfand-Kirillov dimension of L being at most one, though this is no longer true for infinite graphs. It is shown that, for an arbitrary graph E, the Leavitt path algebra L has Gelfand-Kirillov dimension zero if and only if E has no cycles. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
1
1
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…Examples show that the converse of these statements do not hold. Interestingly, it turns out that the graphical conditions on E that ensure L has a bounded index of nilpotence are exactly the same graphical conditions on E that were shown in [4] to imply that L satisfies a polynomial identity. When E is a finite graph, these graphical conditions also imply that L has GK-dimension ≤ 1.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…Examples show that the converse of these statements do not hold. Interestingly, it turns out that the graphical conditions on E that ensure L has a bounded index of nilpotence are exactly the same graphical conditions on E that were shown in [4] to imply that L satisfies a polynomial identity. When E is a finite graph, these graphical conditions also imply that L has GK-dimension ≤ 1.…”
Section: Introductionmentioning
confidence: 65%
“…For instance, the Amitsur-Levitzky theorem (see [13]) states that, for any n ≥ 1, the matrix ring M n (R) over a commutative ring R satisfies a polynomial identity of degree 2n. In [4] it is shown that the Leavitt path algebra L K (E) of an arbitrary graph E over a field K satisfies a polynomial identity if and only if no cycle in E has an exit and there is a fixed positive integer d such that the number of distinct paths that end at any given vertex v (including v, but not including the entire cycle c in case v lies on c) is less than or equal to d. When E is a finite graph, then the Leavitt path algebra L K (E) satisfying a polynomial identity is known to be equivalent to the Gelfand-Kirillov dimension of L K (E) being at most one [4]. (1) L has index of nilpotence less than or equal to n;…”
Section: Resultsmentioning
confidence: 99%
“…Theorem 4.7 ( [9], [17], [25], [27], [28], [43] ) For a finite graph E, the following conditions are equivalent for L := L K (E):…”
Section: An Interesting History Of Conditions (K) and (L)mentioning
confidence: 99%
“…A Γ-graded ring R is said to be a graded Baer ring, if the left/right annihilator of every subset X of homogeneous elements is generated by a homogeneous idempotent. A ring R is said to have bounded index of nilpotence if there is a positive integer n which is such that a n = 0 for every nilpotent element a ∈ R. Theorem 4.7 ( [9], [17], [25], [27], [28], [43] ) For a finite graph E, the following conditions are equivalent for L := L K (E):…”
Section: Four Important Graphical Conditionsmentioning
confidence: 99%
See 1 more Smart Citation